(untitled) (Transactions of the Association of European Schools of Planning, 2022)
This paper presents the results of a comparative research on place-based policies towards “left-behind territories” in Europe. It shows the variety of trajectories of putting the territorial question on the agenda and of defining the ’forgotten’ territories in Italy, Spain and Poland. This variety reveals specific processes linked to short- and long-term debates on the Nation. The tools used to help these territories tend to converge, under the influence of methods coming from the European Union. However, the functions of these territories are still unclear in national planning strategies, particularly because their possible contributions to ecological transition and the economic models of this transition are only imperfectly defined.